In situ catalyzed and nanoconfined magnesium hydride nanocrystals in a Ni-MOF scaffold for hydrogen storage. Issue 9 (15th July 2020) - Ma, Zhewen; Zhang, Qiuyu; Panda, Subrata; Zhu, Wen; Sun, Fengzhan; Khan, Darvaish; Dong, Jinjian; Ding, Wenjiang; Zou, Jianxin
Abstract : Nanostructured Mg2 NiH4 in situ formed around nanoconfined MgH2 crystals (top) and the superior thermodynamic and kinetic properties of MgH2 @Ni-MOF (bottom). Abstract : Nano-confinement (NC) of Mg/MgH2 in suitable host materials is a promising strategy for simultaneously tuning the thermodynamics and kinetics of Mg-based hydride materials. In the present study, the fabrication of multifunctional host materials for NC of MgH2 was firstly attempted with the aim of improving the hydrogen sorption properties of MgH2 . The NC of MgH2 in the mesoporous structure of a Ni-based metal–organic-framework (denoted as MgH2 @Ni-MOF) was successfully conducted via a combination of solvothermal method and wet impregnation method followed by hydrogenation at relatively lower temperatures. Structural inspections through X-ray diffraction and high resolution transmission electron microscopy demonstrate the in situ formation of Mg2 NiH4 around the MgH2 nanocrystals (∼3 nm), due to the reaction between Ni ions from the Ni-MOF and Mg ions from the dibutyl-magnesium (MgBu2 ) precursor in a hydrogen atmosphere. Hydrogen sorption tests reveal that the thermodynamics (−65.7 ± 2.1 and 69.7 ± 2.7 kJ mol −1 H2 for ab-/desorption, respectively) and kinetics (41.5 ± 3.7 and 144.7 ± 7.8 kJ mol −1 H2 for ab-/desorption, respectively) of Mg/MgH2 in the MgH2 @Ni-MOF composite have been significantly improved. Meanwhile, the Ni-MOF scaffold acts as an "aggregation blocker" to impede the growth and agglomeration of Mg/MgH2 nanocrystals during hydriding/dehydriding cycles, leading to outstanding hydrogen cycling stability. The improvement in thermodynamics and kinetics of MgH2 @Ni-MOF has been attributed to the synergistic "nanosize effect" of nanoconfined Mg/MgH2 and catalytic effects from in situ formed Mg2 Ni/Mg2 NiH4 .